SHP-1 and SHP-2 gene expressions in leukemia and unclassified blood disorders - May, Nguyen Thi; Xuan, Nguyen Thi (Academia Journal of Biology, 2020)
Hematopoiesis and blood diseases include leukemia and unclassified blood disorders (UBDs). Leukemia, one of the leading causes of cancer death in the world, is divided into four major types including acute lymphocytic leukemia (ALL), chronic lymphocytic leukemia (CLL), acute myeloid leukemia (AML) and chronic myeloid leukemia (CML). The SHP gene group belongs to the protein tyrosine phosphatase (PTP) family, which plays an important role in preventing cancer growth. This group consists of two main genes, SHP-1 and SHP-2. In this study, experiments were conducted to determine the expression of SHP-1 and SHP-2 genes in patients with leukemia and UBDs using real-time PCR. Results showed that while SHP-1 gene expression was significantly decreased in all patient samples compared to control samples, SHP-2 gene expression was significantly increased in patients with CML and other blood disorders but decreased in ALL patients compared to healthy subjects. These results are important for disease diagnosis and combination therapy based on SHP-1 and SHP-2 target genes.